Culturas Políticas em Angola e Moçambique. Elementos para uma agenda de investigação - Franz-Wilhelm Heimer; Elisete Marques da Silva (Cadernos de Estudos Africanos)
These notes have two purposes. On the one hand, they draw the attention to the importance of including the subjective dimension in the analysis of the politicai processes in Africa, and to do so by using adequate tools. On the other hand, they present research findings obtained through open interviews, during the exploratory phase of an inquiry into contemporary politicai cultures in Angola and Mozambique. The text describes the salience given by the interviewees to politicai values and dif ferent types of social representations of politics, and the affective attitudes resulting from both. It also points out differences which seem to emerge between the two countries included in the study, and formulates generic conclusions for the systematical research the authors intend to carry out.